PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INVESTIGATION DENGAN PENDEKATAN OPEN ENDED PROBLEM UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS - Sirad, La Ode; Susanti, Gemi; Adawiah, Rasidahtul (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2020)
The purpose of this research is to improve the ability of mathematical representation of Grade VIII2 students at SMP Negeri 3 Raha 2018/2019 Academic Year during mathematics learning activities with the application of cooperative learning model in the type group investigation with open ended problem approach. The type of research is classroom researh of two cycles based on teaching syllabus of the mathematics teacher in class VIII2. Each cycle is carried ot based on the competency standards to be achieved in learning. The cycle in this class action research through four stages, namely : planning of action; implementation of action; observation and evaluation; reflection. Based on the result of research conducted on the Grade VIII2 students at SMP Negeri 3 Raha 2018/2019 Academic Year on the competency standards: calculating area and volume of prism and pyramid using cooperative learning model in the type group investigation with open ended problem approach can improve the ability of mathematical representation, which are : respones and learning outcomes shown in cycle II are primly goodand the students scoreof mathematical representation test capability in each cycle has improve signivicantly, until 80% on the last cycle. Moreover, the results showed that there are only 4 students from total 20 students who obtain score 68 which is the minimum completeness criteria set by the school . Student activities and learning management by the teacher in the learning process also increased to cycle II reaching an average of 82% and 81%. Therefore, learning by applying cooperative learning model in the type group investigation with open ended problem approach can improve the ability of mathematical representation